ANALISIS JENIS KALIGRAFI ARAB DI MASJID AGUNG AL-FALAH KOTA JAMBI - Azizah, Drs. Syafei, M.Ag, Yofita sandra, S.Pd, M.Pd (Serupa The Journal of Art Education, 2014)
Masjid Agung Al-Falah is one of the biggest Masjid in Jambi, that we called with 1000 pole Masjid. This Masjid were build on 1971 and finished on 1980. The peculiarity from this Masjid is have the cupola that decorated with Holy Qur’an verse calligraphy which have gold yellow panted with yellow, brown, and green background.This research aimed to know the kind of Arabic Calligraphy that used in Masjid Al-Falah, Jambi. The research was a qualitative research with descriptive method. This research was held for 2 months, started from June 2013 until July 2013. The data were analyzed used field research, observation, interview, and documentation.The result showed some visual elements that found in Masjid Agung Al-Falah’ calligraphy, such as it is materials, the type of calligraphy, the color, and the hand writing elements. The type of calligraphy that found in Masjid Agung Al-Falah, Jambi such: Tsulus, Kufi, and Riqaah. The common placement of this calligraphy is in the mihrab and prime room. The factor of calligraphy selection dive to the consideration of calligraphy in the art sector, religion, and culture. From the result of that invention are suggested for the organizer to increase the art of calligraphy and ought to maintain the local culture elements while choosing beside the religion, art, and aesthetics value. While choosing the holy Qur’an verses the organizer of masjid have to pay attention to the superiority of the verse than the art of calligraphy. Kata kunci: Jenis Kaligrafi Arab